Bias-Variance Tradeoffs in Program Analysis - Aiken, Alex; Nori, Aditya; Sharma, Rahul (Principles of Programming Languages (POPL), 2014)
It is often the case that increasing the precision of a program analysis leads to worse results. It is our thesis that this phenomenon is the result of fundamental limits on the ability to use precise abstract domains as the basis for inferring strong invariants of programs. We show that bias-variance tradeoff, an idea from learning theory, can be used to explain why more precise abstractions do not necessarily lead to better results and also provides practical techniques for coping with such limitations. Learning theory captures precision using a combinatorial quantity called the VC dimension. We compute the VC dimension for different abstractions and report on its usefulness as a precision metric for program analyses. We evaluate cross validation, a technique for addressing bias-variance tradeoffs, on an industrial strength verification tool. The tool produced using cross validation has significantly better running time, finds new defects, and has fewer time-outs than the current production version. Finally, we make some recommendations for tackling bias-variance tradeoffs in program analysis.